At the dawn of history: From Iron Age aggrandisers to Zhenla kings. (26th September 2016) - Higham, Charles F.W.
Abstract : The transition from Late Iron Age to early state societies in the riverine lowlands of the Mun Valley and northern Cambodia took place rapidly in the fifth and sixth centuries CE. Defining the former involves archaeological excavation, whereas the latter is best known from surviving temple structures and inscriptions in addition to the results of archaeological fieldwork. Several common threads link the two phases of cultural development. From the late fifth century BCE, Iron Age communities participated in the growing maritime exchange network linking Southeast Asia with China and India, bringing exotic ideas and goods into the hinterland. Iron itself had a major impact on agriculture and warfare. Salt, a vital commodity that is abundantly available in the Mun Valley, was exploited on an industrial scale. By the fifth century CE, an agricultural revolution involving permanent, probably irrigated, rice fields and ploughing underwrote a rapid rise of social elites. These leaders in society, named in the early historic inscriptions, maintained and elaborated prehistoric innovations.